TRANSFORMASI PENDIDIKAN BERKARAKTER MENUJU GENERASI EMAS 2045: ANALISIS PEMIKIRAN DALAM BUKU SEKOLAH MASA DEPAN - Juwita, Rahmi; Purwoko, Lukman Fajar; Amliansyah, Amliansyah; Fradana, Aldi; Sandi, Deka Maita (Jurnal Manajemen Pendidikan, 2025)
Objective: This paper discusses the increasingly complex challenges of 21st century education. In 2045, it is estimated that the world economy will no longer depend on the economic movement of the United States (US). However, it is estimated that the economic center will move to Asia due to several supporting factors. Therefore, it is necessary to modify the education system, perspective on human resources, and the mindset, seriousness and involvement of all stakeholders. Methods: The approach used is qualitative, data collection is carried out through a library research. Results This transformation will be carried out using three strategies, namely: First, focus on the school of the future framework. Second, providing new innovations for curriculum development based on local potential, and third accommodating the two previous strategies, namely strengthening potential-based characters. Novelty: 1) Conceptual: Integration of 21st Century Character and Competence; 2) Contextual: This article combines local potential as a basis for transformation; 3) Methodological: Analysis of the book "Future School" as a reflective model has never been written in previous articles; 4) In addition, strategic novelty: Synergy between the school ecosystem and the social ecosystem.